New Voters and Old Voters: Understanding Volatility in Quebecers’ Federal Election Votes between 2008 and 2019 - Embree, Robert; Westlake, Daniel (Canadian Journal of Political Science, 2023)
Federal elections between 2008 and 2019 saw a great of volatility in Quebec, with important consequences for election outcomes. The surge in New Democratic Party (NDP) support in Quebec led the party to official opposition, while Liberal gains in 2011 led the party to a majority government, and Bloc Québécois gains in 2019 helped to reduce the Liberals to a minority. To what extent was this volatility driven by voters switching parties and to what degree was it driven by voters entering and exiting the electorate? This article uses ecological inference based on riding-level data to examine the dynamics of party competition in Quebec from 2008 to 2019. We show that while voter mobilization mattered to volatility, vote switching was the important driver of changing party fortunes during this period., RésuméLes élections fédérales entre 2008 et 2019 ont connu une grande volatilité au Québec, avec des conséquences importantes sur les résultats électoraux. La poussée du soutien du NPD au Québec a conduit le parti à l'opposition officielle, tandis que les gains des libéraux en 2011 ont conduit le parti à un gouvernement majoritaire et que les gains du Bloc Québécois en 2019 ont contribué à réduire les libéraux à une minorité. Dans quelle mesure cette volatilité est-elle due au fait que les électeurs changent de parti et dans quelle mesure est-elle due au fait que les électeurs entrent et sortent de l'électorat ? Cet article utilise l'inférence écologique basée sur des données au niveau des circonscriptions pour examiner la dynamique de la concurrence entre les partis au Québec de 2008 à 2019. Nous montrons que, bien que la mobilisation des électeurs ait joué un rôle dans la volatilité, le changement de parti a été le principal moteur de l'évolution de la situation des partis au cours de cette période.